A De Novo‐Designed Type 3 Copper Protein Tunes Catechol Substrate Recognition and Reactivity. Issue 1 (29th November 2022) - Pirro, Fabio; La Gatta, Salvatore; Arrigoni, Federica; Famulari, Antonino; Maglio, Ornella; Del Vecchio, Pompea; Chiesa, Mario; De Gioia, Luca; Bertini, Luca; Chino, Marco; Nastri, Flavia; Lombardi, Angela
Abstract: De novo metalloprotein design is a remarkable approach to shape protein scaffolds toward specific functions. Here, we report the design and characterization of Due Rame 1 (DR1), a de novo designed protein housing a di‐copper site and mimicking the Type 3 (T3) copper‐containing polyphenol oxidases (PPOs). To achieve this goal, we hierarchically designed the first and the second di‐metal coordination spheres to engineer the di‐copper site into a simple four‐helix bundle scaffold. Spectroscopic, thermodynamic, and functional characterization revealed that DR1 recapitulates the T3 copper site, supporting different copper redox states, and being active in the O2 ‐dependent oxidation of catechols to o ‐quinones. Careful design of the residues lining the substrate access site endows DR1 with substrate recognition, as revealed by Hammet analysis and computational studies on substituted catechols. This study represents a premier example in the construction of a functional T3 copper site into a designed four‐helix bundle protein. Abstract : By properly engineering the first and second coordination sphere, an artificial type 3 di‐copper polyphenol oxidase was obtained. Shaping the active site accessibility, the four‐helix bundle di‐copper DR1 was endowed with enzyme‐like substrate selectivity. DFT computations and experimental investigations showed the key role of the residues lining the active site pocket in tuning substrate recognition by weak interactions.